The bees of the genus Sphecodes Latreille 1804 of the Russian Far East, with key to species (Hymenoptera: Apoidea: Halictidae) - Astafurova, Yulia V.; Proshchalykin, Maxim Yu. (Zootaxa, 2014)
Eighteen species of the bee genus Sphecodes are recorded from the Russian Far East. Sphecodes orientalis Astafurova & Proshchalykin, sp. nov. is described from Primorskiy Territory, Jewish Autonomous Province, Khabarovsk Territory and Sakhalin. Five species: S. laticaudatus Tsuneki 1983, S. nippon Meyer 1922, S. okuyetsu Tsuneki 1983, S. simillimus Smith 1873, and S. tanoi Tsuneki 1983 are recorded for the first time from Russia. Six species: S. albilabris (Fabricius 1793), S. cristatus Hagens 1882, S. longulus Hagens 1882, S. miniatus Hagens 1882, S. monilicornis (Kirby 1802), and S. puncticeps Thomson 1870 are newly recorded from the Russian Far East. New synonymy has been established for S. crassus Thomson 1870 (=S. dyozankeanus Tsuneki 1983, syn. nov.; =S. ohdeyamanus Tsuneki 1984, syn. nov.); S. ferruginatus Hagens 1882 (=S. koikensis Tsuneki 1983, syn. nov.; =S. hanedai Tsuneki 1983, syn. nov.); S. geoffrellus (Kirby 1802) (=S. silvicola Tsuneki 1983, syn. nov.); S. tanoi Tsuneki 1983 (=S. coptis Tsuneki 1983, syn. nov.); S. longulus Hagens 1882 (=S. amakusensis Yasumatsu et Hirashima 1951, syn. nov.); S. scabricollis Wesmael 1835 (=S. sibiricus Cockerell, 1924, syn. nov.). Illustrated key to males and females of all species known from the Russian Far East are provided.